Aims of problem based-learning In teaching future specialists (Eurasian Journal of Philology Science and Education, 2018)
The given article considers the questions of methods of teaching a foreign language, particularly, oneof the varieties of innovative methods of teaching as problem-based learning, which is aimed at formingself-directed independent students. Thismethod of teaching meets the present-day requirements as teaching by researching as well as researching by teaching. With the help of this method we can develop acreative personality, thus, perform the main pedagogic task. Today graduates need to be self-directed andpossess lifelong learning skills. Problem-based learning involve not only active learning but also the formulation and solution of new, non-standard and original tasks. They need to be critical thinkers, problemsolvers and analytical in their approach. It means that learners need to be able to integrate knowledge andskills from a number of disciplines as well as have the interpersonal skills to be an effective team member